Psychological consultation apps in Saudi Arabia: A study for experts’ evaluation and users’ points of view - Abdulmohsen Saud Albesher; Maymunah Faheem Alwahib (PLoS ONE, 2025)
Medical consultation applications (apps) have rapidly proliferated globally. One type of app is the psychological consultation app, which has made visiting doctors more convenient, particularly for individuals who feel embarrassed about consulting a psychiatrist. However, only a few researchers have examined the usability or user experience of such apps. This study aims to evaluate the user experience of psychological consultation apps in Saudi Arabia, specifically focusing on the usability aspects and user satisfaction of the apps “Labayh,” “Estenarah,” and “Mind.” The research employs two methodologies: First, an expert evaluation using the SMART heuristic framework, developed to assess the usability of mobile apps by identifying usability issues based on established principles. Results from this method revealed that all three apps faced challenges, particularly in SMART 5 (Each interface should focus on one task) and SMART 10 (Cater for diverse mobile environments). Second, a sentiment analysis of user reviews from app stores was conducted, categorizing feedback into positive and negative reviews. User reviews were collected using Heedzy, an online tool designed for extracting reviews from mobile apps. Data cleaning was performed using Python libraries, which handled missing data and removed duplicate entries. Out of 459 reviews analyzed, 51% were negative, focusing primarily on general dissatisfaction and functionality issues, while 49% were positive, highlighting user appreciation and the innovative concept of online consultations. Specific findings indicated that the “Mind” app had significant usability concerns, receiving a severity rating of 70, with notable issues in error prevention and interface clarity. Recommendations for improvement include enhancing task-focused design, increasing adaptability for diverse mobile environments, and addressing user feedback to refine app functionalities. This research contributes valuable insights for designers aiming to improve the usability of psychological consultation apps in the region.